Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in Nondialysis Chronic Kidney Patients - Gysllene M. C. Brito; Andrea M. M. Fontenele; Erika Cristina R. L. Carneiro; Iara Antonia L. Nogueira; Tamires B. Cavalcante; André A. M. Vale; Sally Cristina M. Monteiro; Natalino Salgado Filho (International Journal of Inflammation)
Background. The Neutrophil-to-Lymphocyte Ratio (NLR) and the Platelet-to-Lymphocyte Ratio (PLR) are inflammatory biomarkers for several diseases, such as cancer and cardiovascular morbidities; however, there are currently few studies on kidney diseases. We aimed to evaluate nondialysis patients and determine the association of NLR and PLR with inflammation in these patients. Methods. A prospective cross-sectional study was conducted with 85 patients at different stages of chronic kidney disease (CKD), treated at the Kidney Disease Prevention Center of the University Hospital of the Federal University of Maranhão. This study included adult nondialysis patients diagnosed with CKD. The participants’ blood samples were collected for a high-sensitivity C-reactive protein (hs-CRP) test and blood count. They were divided into two groups according to the presence or absence of inflammation based on the hs-CRP value (<0.5 mg/dL). NLR and PLR were calculated based on the absolute number of neutrophils, lymphocytes, and platelets and were compared between them and with hs-CRP. Statistical analysis was performed using the Stata software, with the Shapiro–Wilk, Mann–Whitney, Spearman’s Correlation, and receiver operating characteristic curve tests. This study was approved by the local ethics committee. Results. The participants were categorized into two groups: with inflammation (n = 64) and without inflammation (n = 21). The mean age was 61.43 ± 14.63 y. The NLR and PLR values were significantly different between the groups with and without inflammation (p=0.045and p=0.004, respectively). However, only PLR showed a significant positive correlation with hs-CRP (p=0.015). The best cutoff point for NLR to detect inflammation was 1.98, with 76.19% sensitivity and 48.44% specificity. For PLR, it was 116.07, with 85.71% sensitivity and 51.56% specificity. There was no significant difference between the area under the NLR and PLR curve (0.71 vs. 0.64; p=0.186) for this population. Conclusions. This study showed that PLR was positively correlated with hs-CRP in nondialysis CKD patients and can be used to identify inflammation in this population.